Volunteer Motivation in Firefighting Organisations: A Case of the Slovenian Firefighters Association - Tatjana Kozjek; Uroška Zorec Klemenčič; Lan Umek (Fire)
Volunteer firefighters play an important role in the provision of emergency services in Slovenia, where most of firefighters work on a voluntary basis. In many countries, however, volunteering is in decline due to demographic, social and organisational constraints. To maintain this important function, it is important to understand the motivations that drive individuals to join and stay in the volunteer fire service. This study examines the motivational factors that influence Slovenian volunteer firefighters, with a particular focus on fire service support, leadership practices and demographic differences. A quantitative survey was conducted among 244 volunteer firefighters from 22 fire brigades. The data were analysed using descriptive statistics, t-tests, Spearman’s rank correlation and binary logistic regression. The results show that many volunteer firefighters are motivated by the challenge of working under stress and in situations of controlled risk. However, this motivation decreases with age, as older members show less interest in adrenaline-driven tasks. Men show a greater preference for action-oriented tasks, including emergency response, equipment handling and physical engagement. In contrast, women place slightly more emphasis on social connections within the brigade. Volunteers who feel included in decision-making processes and experience cooperative, participative leadership are more likely to remain engaged. Those who are motivated by physical activity are more likely to stay, while those who are primarily motivated by social recognition or status are more likely to leave. These findings contribute to the literature on volunteering in high-risk contexts. Tailored recruitment and retention strategies that take into account age, gender and leadership dynamics can help fire services build more engaged and sustainable volunteer teams.